EFFECT OF PRO-POOR INITIATIVES FOR EMPOWERMENT OF RURAL WOMEN - PRIYA SUGANDHI, SARAH KAMALA and (The Journal of Research, PJTSAU, 2019)
Women in rural areas are more vulnerable than urban in health related initiatives which are related to knowledge and awareness. Health Initiatives is willingness within the people to help themselves through self-help to collectively think, discuss and act on issues related to health. The South Asia Poverty Alleviation Programme (SAPAP) was implemented by the United Nations Development Programme (UNDP) in the form of pilot projects in six countries in South Asia. Its objective was to demonstrate to governments in the region the feasibility of using the approach of social mobilization to combat rural poverty. The present study conducted in the piloted South Asia Poverty Alleviation Programme (SAPAP) implemented by Government, in three drought–prone disticts viz.Mahaboobnagar, Kurnool, and Ananthapur. The approach and strategy of health initiatives followed was in consonance and congruence with broader conceptual framework of the main poverty alleviation programme, which was based on the premise and conviction that ‘willingness within the people to help themselves’ by developing community based health initiatives in which the community fully participated and was involved at every stage. The data was collected from 180 women SHG beneficiaries of 60 SHGs from 12 villages, to know their perception levels on Health Initiatives. The study concludes that rural women of SAPAP had both positive and negative relationships with health initiatives and socio economic factors.